Proceso de atención de enfermería en paciente de 10 años con fractura supracondílea de fémur izquierdo en el hospital del niño “Dr. Francisco de Icaza Bustamante” de la ciudad de Guayaquil - Contreras Santillán, Vanessa Lisseth (2018)
The present case study modality complex examination (Practical Dimension), performs an analysis and description of the signs and symptoms caused by a fracture and what are the actions to be performed by the nursing staff, applying the Nursing Care Process to reduce complications of the pathology. The supracondylar femur fracture is a complex lesion that often causes a degree of disability in the knee. Emphasis is placed on the need to restore the patient's health by applying strategies to achieve the proposed objectives, establishing the appropriate nursing diagnoses to apply the specific interventions and improve the quality of life of the patient. The justification of the subject is proposed and objectives are proposed that allow us to have a clear goal to act in an effective and timely manner before the fracture, since it is a pediatric patient and the care must be thorough to avoid future complications. The complementary exams provide important information that can define a clear diagnosis, by means of the assessment the altered functional patterns are determined and an adaptation model is implemented. The doctor prescribes analgesics to alleviate the symptoms in the patient since due to the fracture he presents pain EVA 10/10. Evaluation of the applied interventions is carried out and compared with the fulfillment of objectives that are detailed in the conclusion where high posts recommendations are stated for the good management of the wound in the patient.